(untitled) (Journal of Nuclear Technology in Applied Science, 2020)
The latent delayed toxicity for two botanical Camphore and Jamson weed grass fine dusts on Agrotis ipsilon were studied. Whereas, all the evaluated rates of Camphor grass were highly efficient and the number of alive larvae ranged between 6 and 13 larvae out of 30 larvae compared to the untreated check (28 larvae). Furthermore, the delayed results clearly indicated the significant difference between the tested rates and their effect on the raised larvae and revealed its adverse biophysiological effects on the development of both (F1) and (F2) generation that followed by a complete failure of (F3) generation, compared to the untreated check.The tested rates of Jimson weed grass fine dust caused significant reduction of the mean numbers in the surviving alive larvae of A. ipsilon and shows rapid complete failure to the development of the parent generation after larval treatment.Finally , the obtained data showed the effectiveness of the mixture of each Jimson weed with Camphor at a rate of (3:1) and (3:3) gm. fine dusts on the developmental sequence of the larvae of the parent generation that were exposed to the prepared baits. Therefore, the aim of this study is to find alternative methods to reduce the effect of chemical pesticides on the environment.